Recognition of Blow Foraminifera Zones in the Tertiary Sediments in F- Well, Niger Delta - F.A. Lucas; O.E. Ononeme (Journal of Applied Sciences and Environmental Management)
Foraminiferal Micropaleontology of Tertiary sediment in F-Well Niger Delta Basin were carried out using foraminiferal biostratigraphy as geologic tools. Sedimentological description was carried out on 679 ditch cutting samples which aided the erection of 103 lithozones. Fifty (50) ditch cutting samples was used with the aim of establishing the Foraminiferal Biozones and age of the well. A total of eighty (80) foraminiferal species were recorded, most of the species recorded are calcareous and arenaceous benthic  foraminiferal species. They were about twenty-eight (28) diagnostic foraminifera recognized. The evaluation of these foraminifera species enabled us to recognize the zones. The foraminiferal abundances revealed two bio zones N4-N3 Planktic zone and N3 – N2 Planktic zone which were suggested based on index species among the recovered foraminiferal assemblages. N4-N3 Planktic zone has a reference interval of 8,000ft – 9,400ft. The top of this zonal interval which ought to be marked by the FDO of Ammonia becarril was absent but was estimated to be 8,000ft. The base of this zonal interval is marked by the LDO of Epistominella vitriea at 9,400ft. Planktic zone N3 – N2 has a reference interval of 9,400ft – 10,000ft. The top of this interval is marked by the FDO of Bolivina imperatrix at 9,400 ft. The base of this interval is marked by the LDO of Spirosplectamina wrightii at 10,000 ft. The studied intervals in the wells are dated Early Miocene - Oligoocene. Using the lithologic and foraminiferal studies, it is inferred that the intervals penetrated by the well correspond to Agbada Formation.